Prediksi Produktivitas Padi di Provinsi Nusa Tenggara Barat Tahun 2025 Menggunakan Metode Regresi Linear Berdasarkan Data Tahun 2019–2024 - Alya Yayan Apriyandi; Baiq Fiky Renita (Lembaga Publikasi Ilmiah Nusantara, 2026)
This study examines fluctuations in rice productivity in West Nusa Tenggara Province during the period 2019–2024. The issue is important because rice productivity is directly related to production planning, food availability, and regional food security strategies. This study aims to analyze the effects of harvested area and rice production on rice productivity and to develop a prediction model using Multiple Linear Regression. The data used in this research are secondary data obtained from official publications of Statistics Indonesia (BPS), covering three main variables: harvested area, rice production, and rice productivity. The research stages include data collection, data cleaning, productivity calculation, descriptive statistical analysis, regression modeling, model evaluation, and interpretation of results. The analysis indicates that harvested area and rice production simultaneously explain variations in rice productivity with a very high coefficient of determination. The production coefficient is positive, while the harvested area coefficient is negative in the model, indicating that increased production without proportional expansion of harvested area tends to improve productivity. The resulting model can serve as an initial data-driven approach to support agricultural planning, although future research should incorporate climate, irrigation, fertilizer application, seed variety, and cultivation technology variables to improve prediction accuracy.